Functional and histological changes of the pancreas and the liver in the rats after the acute and subacute administration of diazinon - Ivanović, Saša R.; Borzan, Nevena; Janković, Radmila; Ćupić Miladinović, Dejana; Savić, Mila; Ćupić, Vitomir; Borozan, Sunčica (Vojnosanitetski pregled, 2021)
Background/Aim. Organophosphate pesticides (OPs) are used extensively worldwide in agriculture and forestry, and their application represents a major health problem for humans and animals. The aim of this study was to investigate the possibility of the adaptation of an organism to the prolonged administration of a low dose of diazinon. Methods. The study was conducted on a total of 60 male Wistar rats. The first 30 rats were divided into four equal diazinon groups (n = 6) and the control one (corn oil). Diazinon was orally administered once at doses: 200, 400, 600, 800 mg/kg (one dose – one group). The concentration of glucose, the activity of α-amylase and the relative activity of LDH1-LDH5 isoenzymes in the blood were measured 24 hours after the application. The remaining 30 rats were divided into two equal diazinon groups (n = 10) and the control one (corn oil). The first group was treated during 7 days, and the second during 14 days with 55 mg/kg of diazinon (1/10 of previously determined LD50 value). The histopathology of the pancreas and the liver, as well as the relative activities of LDH isoenzymes in the blood, were determined after the completion of both time periods. Results. Single administration of increasing doses of diazinon resulted in a significant increase in the concentrations of glucose, activity of α-amylase and LDH isoenzymes. Subacute application of a low diazinon dose induced histopathological changes in the pancreas manifested by acinar cell necrosis, and in the liver in the form of portal hepatitis and multifocal necrosis. The cumulative doses resulted in statistically significantly lower activities of LDH isoenzymes compared with the single administration of these doses, indicating a lower degree of the cells damage after the subacute diazinon administration. Conclusion. Subacute administration of a low dose of diazinon leads to a different adaptation degree of organs and organ systems to toxic effects caused by this organophosphate.
Keywords: diazinon; histological techniques; liver; organophosphorus compounds; pancreas; rats; toxicity test, subacute